ANALISIS HUBUNGAN JANGKA PANJANG DAN JANGKA PENDEK ANTARA NPL, ROE, SIZE DAN LOTA TERHADAP CAPITAL BUFFER - Juni Purwati (Faculty of Economics and Business Universitas Jenderal Soedirman, 2015)
This study aimed to analyze the effect of Non-Performing Loans, Return onEquity, bank size, and Loan to Total Assets of the capital buffer using panel data. Thepopulation in this study was State Owned Banks registered in Bank Indonesia for theperiod 2002 to 2014. In this study all the population used as an object of study and thetype of data used in this research was quarterly data.Data were analyzed using cointegration test and Error Correction Model todemonstrate short and long term relationship. The results showed that in the short term,the Non Performing Loan and Return on Equity have a positive influence onequilibrium of capital buffers in goverment bank. Furthermore, the size of banknegatively affect the equilibrium of capital buffers in the short term. Besides the longterm relationship, the Non Performing Loan and Return on Equity also has a positiveeffect on the equilibrium of capital buffers in state-owned commercial banks.Meanwhile, Loan to Total Assets have a negative effect on the equilibrium of capitalbuffers in the long term